2018
DOI: 10.1159/000487801
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Multiple Neuroimaging Markers using Logistic Regression for Auxiliary Diagnosis of Alzheimer Disease and Mild Cognitive Impairment

Abstract: Background: Multiple neuroimaging modalities have been developed providing various aspects of information on the human brain. Objective: Used together and properly, these complementary multimodal neuroimaging data integrate multisource information which can facilitate a diagnosis and improve the diagnostic accuracy. Methods: In this study, 3 types of brain imaging data (sMRI, FDG-PET, and florbetapir-PET) were fused in the hope to improve diagnostic accuracy, and multivariate methods (logistic regression) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
(37 reference statements)
1
5
0
Order By: Relevance
“…The AUC value tended to be higher in the model with FDG‐PET and the MMSE score than in the model with the MMSE score alone. This was consistent with findings of a previous study reporting that FDG‐PET might be more effective than amyloid PET and MRI in discriminating individuals with MCI from controls . Furthermore, FDG‐PET can detect cognitive decline‐associated early changes in AD with high sensitivity compared with MRI .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The AUC value tended to be higher in the model with FDG‐PET and the MMSE score than in the model with the MMSE score alone. This was consistent with findings of a previous study reporting that FDG‐PET might be more effective than amyloid PET and MRI in discriminating individuals with MCI from controls . Furthermore, FDG‐PET can detect cognitive decline‐associated early changes in AD with high sensitivity compared with MRI .…”
Section: Discussionsupporting
confidence: 91%
“…Although the AUC value was significantly higher in the model with all three modalities than in the model with the MMSE score alone or in the model with MRI in addition to the MMSE score, the combination of all three modalities achieved the highest AUC for discrimination accuracy. Few studies have investigated the utility of combining MRI, FDG‐PET and amyloid PET for the diagnosis of amnestic MCI . One study compared the accuracy of identifying MCI or AD among combinations of these three imaging methods using logistic regression analysis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that their applied classification algorithm (support vector machine, SVM) could better diagnose patients with mood disorders and accurately predict the drug response of complex patients. Mao et al 12 used a logistic regression method and combined multiple neuroimaging data for the diagnosis of Alzheimer’s disease and mild cognitive impairment. Their results suggested that the use of multiple neuroimaging markers can improve the diseases diagnosis performance.…”
Section: Introductionmentioning
confidence: 99%
“…In SVM, a hyperplane or set of hyperplanes is constructed in a large or infinite-dimensional space and is used for classification (Salvatore et al, 2016). Logistic regression (Mao et al, 2018) is based on a multinomial logistic regression model with a ridge estimator. Random forests are an ensemble learning method for classification based on a multitude of decision trees (Bi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%